A Haversian bone model of fracture healing in a simulated microgravity environment - Gadomski, Benjamin C., author; Puttlitz, Christian M., advisor; Browning, Raymond, committee member; Donahue, Tammy, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2015)
Ground-based models of weightlessness and microgravity have provided valuable insights into how dynamic physiological systems adapt or react to reduced loading. Almost all of these models have used rodent hindlimb unloading as the means to simulate microgravity on isolated physiological systems. Unfortunately, results derived from rodent studies are significantly limited when one tries to translate them to the human condition due to significant anatomical and physiological differences between the two species. Therefore, it is clear that a novel animal model of ground-based weightlessness that is directly translatable to the human condition must be developed in order for substantial progress to be made in the knowledge of how microgravity affects fracture healing. In light of this, four specific aims are proposed: (1) develop a ground-based, ovine model of skeletal unloading in order to simulate weightlessness, (2) interrogate the effects of the simulated microgravity environment on bone fracture healing using this large animal model, (3) develop a computational model of weightbearing in ovine bone under different experimental conditions in order to characterize the loads experienced by the fracture site, and (4) develop countermeasures that enhance bone fracture healing in the presence of simulated microgravity. Successful completion of this project will substantially elevate the understanding of how fracture site loading affects the subsequent healing cascade in the presence of microgravity and will form the foundation for designing future rehabilitation protocols to facilitate bone healing during long-duration spaceflight.
Keywords: fracture healing; sheep; finite element; space; microgravity